A framework for cloud-aware development of bag-of-tasks scientific applications. (2016) - Benedictis, Alessandra De; Rak, Massimiliano; Turtur, Mauro; Villano, Umberto
The potential of cloud computing is still underutilised in the scientific computing field. Even if clouds probably are not fit for high-end HPC applications, they could be profitably used to bring the power of low-cost and scalable parallel computing to the masses. But this requires simple and friendly development environments, able to exploit cloud scalability and to provide fault tolerance. This paper presents a framework built on the top of a cloud-aware platform (mOSAIC) for the development of bag-of-tasks scientific applications. The architecture of the framework is thoroughly described, and the results of performance tests on a combinatorial optimisation application are discussed, evaluating the overhead introduced by the platform and by the cloud environment.